Barriers and drivers to childhood vaccinations in Forcibly Displaced Myanmar Nationals (FDMN)/Rohingya refugees in Cox’s Bazar, Bangladesh: a scoping review - Yusuf, Zarah; Reda, Sarah; Hanefeld, Johanna; Jackson, Cath; Chawla, Balwinder Singh; Jansen, Andreas; Lange, Saskia; Martinez, Jorge; Meyer, Emily Dorothee; Neufeind, Julia; Singh, Aarti Shrikrishana; Wulkotte, Elisa; et al. (Frontiers in Public Health, 2025)
About one million Forcibly Displaced Myanmar Nationals (FDMN)/Rohingya refugees live in the refugee camps of Cox’s Bazar, experiencing recurring vaccine-preventable disease outbreaks despite established vaccination programs. This scoping review focused on the evidence for individual and context barriers, drivers, and interventions for childhood vaccination uptake of FDMN/Rohingya refugees in Cox’s Bazar. Four databases and grey literature were systematically searched. Theoretical frameworks were used to organize findings. 4,014 records were screened, and 21 articles included. The literature was heterogenous. Barriers and drivers for FDMN/Rohingya refugees receiving vaccination focused on motivation relating to trust, beliefs and fears (19 barriers and drivers in 11 articles), accessibility and information availability (19 barriers and drivers in 11 articles), as well as knowledge and ability (eight barriers and drivers in nine articles), and socio-cultural and gender-related norms and social support (seven barriers and drivers in eight articles). For health service providers facilitating vaccinations, context factors, such as the availability of vaccines and staff, were most frequently identified (13 barriers and drivers in 12 articles). Interventions mostly related to vaccination campaigns and information/education. They often lacked detail and formal evaluations. Future research and interventions on childhood vaccination should consider barriers and drivers for health service providers, the diversity of the camp population, and explore the role of community/religious leaders and gender-related social norms. Additionally, the reporting and evaluation of interventions should be strengthened.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/N6D3URL; https://osf.io/n6d3z.